AN ANALYSIS OF MUJAHADAH AN-NAFS IN THE TARBAWI TAFSIR AND ITS RELEVANCE TO SELF-REGULATED LEARNING - Tarsono Tarsono; Siti Jubaedah Ghani; Suci Nurulfadilah; Mahawi Mahawi; Evi Luthfi Nurulhayati (Jurnal Konseling Pendidikan Islam, 2026)
The phenomena of moral degradation, low academic discipline, and weak self-awareness among students pose major challenges for modern education. In this context, self-control (mujahadah an-nafs), as taught in Islam, is strongly relevant to the theory of self-regulated learning (SRL) in educational psychology. This study employs a qualitative approach using a literature review method aimed at analyzing the concept of mujahadah an-nafs in educational exegesis and its relevance to the theory of self-regulated learning. The findings reveal that mujahadah an-nafs, which proceeds through six systematic stages: ma‘rifatul aduww, muraqabah, muhasabah, mu‘aqabah, riyadhah, and istiqamah, demonstrates significant convergence with Zimmerman’s three phases of self-regulated learning (forethought, performance, and self-reflection). These findings yield an integrative model that offers a holistic educational paradigm, overcomes the dichotomy between academic and character education, and provides an applicable framework for developing self-regulated learning grounded in Islamic spiritual values within the context of strengthening the Pancasila Student Profile.